Optimizing clean water filtration through the application of science and technology: Reverse osmosis method - Yuliati, Yuliati; Baharuddin, Alfina; Hardi, Hardi; Astachya Ananda Sofyan, Siti; A. Fachrin, Suharni; Andayanie, Ella (Journal Pengabdian Masyarakat Politeknik Sandi Karsa, 2025)
Water is the fundamental basis for all biological and human activities. Water is believed to be a natural resource that will never run out and will always be available at all times. Nonetheless, the availability of water as a natural resource is restrained due to its relatively constant hydrological cycle; thus making it limited in supply. The methods used during the activity were lectures and discussions. At the beginning of the activity, the team conducted counseling related to well water sanitation and its impact and how to overcome it. The method of this counseling stage is carried out through 5 stages, namely: socialization stage, implementation stage. This activity includes 3 sessions, among others: First stage: Pre test, which is given through a questionnaire, through lecture, question and answer, and discussion methods Post test and assessing the results of the post test, technology application stage, monitoring and evaluation stage, program sustainability stage. The results of the service activities showed that the educational program on access to clean water sanitation and the effects of borehole water for health succeeded in significantly increasing the knowledge of the participants. The average score increased from 19.22 in the pre-test to 21.18 in the post-test, with a p-value of 0.001 which shows a significant difference. This result confirms the effectiveness of the clean water sanitation education program.